Sharia Monetary Policy Instruments in Indonesia - Abi Suar; Zandy Pratama Zain; Hijrasil (JOVISHE : Journal of Visionary Sharia Economy, 2022)
In Islamic monetary policy, there is no known interest system. The instruments used in Islamic monetary policy are also different from monetary policy in general because they are not familiar with the interest system. Precisely with the unknown interest system, making Islamic monetary policy more resistant to economic turmoil so that in the end the ultimate goal of monetary policy can be achieved and will be able to become a new tool in maintaining economic stability. The approach used in this study is Literature review using the Systemic Literature Review (SLR) method. The purpose of this study is to find out how the Islamic Monetary Policy Instrument is defined, mazhab and its implementation in Indonesia.Indonesia as a country that implements a dual monetary system, Indonesia also conducts monetary policy through OMS or Sharia Monetary Operations. Sharia Monetary Operation is the implementation of monetary policy by Bank Indonesia in the context of monetary control through open market operations and the provision of standing facilities based on sharia principles. The objectives of CSOs areachieve the operational target of sharia monetary control in order to support the achievement of the final target of Bank Indonesia's monetary policy. Abstrak Dalam kebijakan moneter Islam, tidak dikenal sistem bunga. Instrumen yang digunakan dalam kebijakan moneter syariah juga berbeda dengan kebijakan moneter pada umumnya karena belum mengenal sistem bunga. Justru dengan tidak dikenalnya sistem bunga membuat kebijakan moneter syariah lebih tahan terhadap gejolak ekonomi sehingga pada akhirnya tujuan akhir kebijakan moneter dapat tercapai dan mampu menjadi alat baru dalam menjaga stabilitas ekonomi. Pendekatan yang digunakan dalam penelitian ini adalah Literature review dengan menggunakan metode Systemic Literature Review (SLR). Tujuan dari penelitian ini adalah untuk mengetahui bagaimana definisi Instrumen Kebijakan Moneter Syariah, mazhab dan implementasinya di Indonesia. Indonesia sebagai negara yang menerapkan sistem moneter ganda, Indonesia juga melakukan kebijakan moneter melalui OMS atau Operasi Moneter Syariah. Operasi Moneter Syariah adalah pelaksanaan kebijakan moneter oleh Bank Indonesia dalam rangka pengendalian moneter melalui operasi pasar terbuka dan pemberian standing facilities berdasarkan prinsip syariah. Tujuan CSO adalah untuk mencapai sasaran operasional pengendalian moneter syariah dalam rangka mendukung pencapaian sasaran akhir kebijakan moneter Bank Indonesia.